AUTOMATIC CHORUS DETECTION FOR INDONESIAN MUSIC USING REFRAIN DETECTING METHOD (REFRAID) - Ichsan Permana Putra; Elvia Budianita; Febi Yanto; Yusra Yusra (Informatika, Universitas Jenderal Soedirman, 2022)
Music has become an important part of human life, chorus is part of the musical structure that makes some impression on music, people are generally very familiar with the chorus in music because the chorus is often repeated on music. Automatic chorus detection is a part of Music Information Retrieval which is considered important for building music analysis system with human-like patterns. Refrain Detecting Method (RefraiD) select the chorus by grouping various repeating parts of the music, evaluating the intensity level of the melody from each group, then selecting the group with the highest melodic intensity as the chorus. This paper intends to implement RefraiD in Indonesian pop and dangdut music by downloading 20 pop music videos and 20 dangdut music videos from YouTube then process it with Information retrieval using Python. The results of this paper indicate that the RefraiD method can be used to detect the chorus on Indonesian music with F measure of 91.8% for dangdut music and 91.5% for pop music.